Study protocol for a randomized controlled trial of Proportional Assist Ventilation for Minimizing the Duration of Mechanical Ventilation: the PROMIZING study - Karen J. Bosma; Claudio M. Martin; Karen E. A. Burns; Jordi Mancebo Cortes; Juan Carlos Suárez Montero; Yoanna Skrobik; Kevin E. Thorpe; Andre Carlos Kajdacsy-Balla Amaral; Yaseen Arabi; John Basmaji; Gaëtan Beduneau; Francois Beloncle; et al. (Trials)
Abstract Background Proportional assist ventilation with load-adjustable gain factors (PAV+) is a mechanical ventilation mode that delivers assistance to breathe in proportion to the patient’s effort. The proportional assistance, called the gain, can be adjusted by the clinician to maintain the patient’s respiratory effort or workload within a normal range. Short-term and physiological benefits of this mode compared to pressure support ventilation (PSV) include better patient-ventilator synchrony and a more physiological response to changes in ventilatory demand. Methods The objective of this multi-centre randomized controlled trial (RCT) is to determine if, for patients with acute respiratory failure, ventilation with PAV+ will result in a shorter time to successful extubation than with PSV. This multi-centre open-label clinical trial plans to involve approximately 20 sites in several continents. Once eligibility is determined, patients must tolerate a short-term PSV trial and either (1) not meet general weaning criteria or (2) fail a 2-min Zero Continuous Positive Airway Pressure (CPAP) Trial using the rapid shallow breathing index, or (3) fail a spontaneous breathing trial (SBT), in this sequence. Then, participants in this study will be randomized to either PSV or PAV+ in a 1:1 ratio. PAV+ will be set according to a target of muscular pressure. The weaning process will be identical in the two arms. Time to liberation will be the primary outcome; ventilator-free days and other outcomes will be measured. Discussion Meta-analyses comparing PAV+ to PSV suggest PAV+ may benefit patients and decrease healthcare costs but no powered study to date has targeted the difficult to wean patient population most likely to benefit from the intervention, or used consistent timing for the implementation of PAV+. Our enrolment strategy, primary outcome measure, and liberation approaches may be useful for studying mechanical ventilation and weaning and can offer important results for patients. Trial registration ClinicalTrials.gov NCT02447692 . Prospectively registered on May 19, 2015.